The implementation and evaluation of a service-learning component in a second year undergraduate organic chemistry course - Abel, Sarah Ruth (Rhodes University, Faculty of Science, Department of Chemistry, 2011)
The project describes the action research implementation, and evaluation of learning, of a service-learning component in a second year undergraduate organic chemistry course. The research aims to explore the learning that takes place in a service-learning context while utilizing an action research methodology within the critical theory paradigm. This occurs in response to the world-wide call for Higher Education to produce people with civic competencies and responsiveness to the society in which they live (Boyer 1996). Educating young Chemists to see the importance of their knowledge and their responsibilities in society is an important pedagogical step in the effort to cross boundaries and make connections between people communities (Eyler and Giles 1999). The goal of this project was to explore and categorize the learning that takes place in a service-learning context and discover how these areas of learning impact the awareness of the parties involved with regard to the discipline of chemistry as well as social issues. The project makes use of Kolb's (1984) Experiential Learning Theory, and Eyler and Giles' (1999) categories of learning in service-learning and results indicate that service-learning can be a powerful pedagogical tool to increase learning in chemistry as well as in the areas of critical thinking, personal and social development, reflection and citizenship. Students' perceptions of themselves, their discipline and their responsibility to society were transformed by their experience of service-learning in their undergraduate chemistry course.
Keywords: Chemistry, Organic -- Study and teaching (Higher) -- South Africa; Action research in education -- South Africa; Experiential learning -- South Africa; Service learning -- South Africa